2011
DOI: 10.1007/s12038-011-9149-3
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia endosymbiont infection in two Indian butterflies and female-biased sex ratio in the Red Pierrot, Talicada nyseus

Abstract: The maternally inherited obligate bacteria Wolbachia is known to infect various lepidopteran insects. However, so far only a few butterfly species harbouring this bacterium have been thoroughly studied. The current study aims to identify the infection status of these bacteria in some of the commonly found butterfly species in India. A total of nine butterfly species belonging to four different families were screened using PCR with Wolbachia-specific wsp and ftsZ primers. The presence of the Wolbachia super gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recently Kodandaramaiah et al [50] observed Wolbachia infection in an entire population of Polygonia c-album (comma butterfly) suggesting existence of strong CI. Ankola et al [51] reported B supergroup Wolbachia in Talicada nyseus and Papilio polymnestor. They further found that Wolbachia infected T. nyseus showing female biased sex ratio and they suggest the possibility of Wolbachia driven MK or feminization as a cause behind this distortion.…”
Section: Wolbachia Diversity In the Butterfliesmentioning
confidence: 99%
“…Recently Kodandaramaiah et al [50] observed Wolbachia infection in an entire population of Polygonia c-album (comma butterfly) suggesting existence of strong CI. Ankola et al [51] reported B supergroup Wolbachia in Talicada nyseus and Papilio polymnestor. They further found that Wolbachia infected T. nyseus showing female biased sex ratio and they suggest the possibility of Wolbachia driven MK or feminization as a cause behind this distortion.…”
Section: Wolbachia Diversity In the Butterfliesmentioning
confidence: 99%
“…Populations of insects might not be infected at all: e.g., weevil Centricnemus leucogrammus [ 40 ] and Cryptocephalus leaf beetles [ 51 ]. On the other hand, some species seemed to be infected across an entire range by the same supergroup and even the same strain: e.g., weevil Polydrusus inustus [ 41 ], Chinese rice leafroller Cnaphalocrocis medinalis [ 15 ], Indian butterflies Talicada nyseus [ 2 ], and leaf beetle Oreina cacaliae [ 51 ]. An alternative example concerns species with populations co-infected by different supergroups and/or strains: e.g., grasshopper Chorthippus parallelus [ 92 ], bean beetles Callosobruchus chinensis [ 43 ], leaf beetle Crioceris quatuordecimpunctata , and Crioceris quinquepunctata [ 44 , 56 ].…”
Section: Introductionmentioning
confidence: 99%